Ablation Behavior of Zr–Al(Si)–C Layered Carbides Modified 3D Needled C/SiC Composites. Issue 6 (17th December 2018) - Ma, Yuzhao; Yin, Xiaowei; Fan, Xiaomeng; Dang, Xiaolin; Ju, Panfei; Cheng, Laifei; Zhang, Litong
Abstract : 3DN C/SiC composites modified through the combined method of slurry impregnation (SI) with reactive melt infiltration (RMI) can obtain obviously improved mechanical properties. However, when used under the oxyacetylene torch ablation environment, metal melt and low melting point oxides usually lead to the low ablative properties. In this paper, Al40 Si60 alloy and Si melt are used to infiltrate 3DN C/SiC preforms impregnated with TiC or ZrC powders, respectively. Large amount of Ti3 Si(Al)C2 or Zr3 Al3 C5 (and Zr3 [Al(Si)]4 C6 ) with nano‐laminated structure generated in the modification matrix, which not only increase the flexural strength of the composites, but also reduce the content of low melting point phases in the modification matrix. These layered carbides can keep steady under air flow, thus further improve material's ablative properties. Meanwhile, during the ablation of Zr–Al(Si)–C layered carbides modify 3D needled C/SiC, the high melting point layered carbides act synergistically with the high melting point ZrO2 generated. They can block the ZrO2 generated from migrating along with the air flow, so that ZrO2 can effectively act its pinning effect on the oxide melt and finally obtain desirable ablative properties. Abstract : 3DN C/SiC and a series of 3DN C/SiC composites modified through combined method of SI and RMI is fabricated for the reveal of their ablative behavors and mechanism. Modification of Zr–Al(Si)–C layered carbides obviously increase the mechanical and ablative property of the composites. Fracture toughness and density of modified 3DN C/SiC are also relevant with the materials' ablative properties.